Design and manufacturing of openwork mannequin-hanger; Modern technique and technologies MTT' 2012 - Pelevin E. A. Evgeniy Aleksandrovich (Section XI: Design and technology of Art Processing of Materials, 2012)
Заглавие с титульного листа